Neuropsychiatric Toxicity of Ifosfamide in Patients Admitted for Chemotherapy - Mohammadali Mashhadi; Alireza Khosravi (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
"nAbstract "nIntroduction: Ifosfamide (IFO) is a potent drug that is used in cancer therapy. The major uses of IFO are: solid tumors especially, osteogenic sarcoma, other soft tissue sarcomas and hematologic malignancy, especially in lymphoma patients. The toxicity of IFO is very encompassing and includes: alopecia, nausea, vomiting, gastrointestinal, renal and neurological problems. Neuropsychiatric toxicities vary and include: fatigue, confusion, coma, and death. An early detection of the neurologic toxicities of IFO and discontinuation of the drug is the best way to manage these side effects. "nMaterials & methods: In a prospective study, on all admitted patients in our ward who had received Ifosfamide for chemotherapy and did not have any underlying disease. After a full physical examination and the performing of necessary paraclinical evaluations, information forms for all of the patients were filled out at admission and in follow up visits to be used in their final assessments. Neuropsychiatry examinations were performed with neuropsychiatric physician. The physician repeated their examinations at the end of treatment. If the patients had any symptoms or signs of neuropsychiatric problems the examinations were repeated examination and documented in their files. "nResults: Sixty- six cases were male and 34 cases were female. The mean age was 36.4 years (18-49). The most common neuropsychiatric side effects were fatigue and delirium. Side effects were observed in 60% of the patients, and other toxicities included: somnolence (20%), confusion (10%), agitation (5%), extrapyramidal symptoms (5%), stupor (8%); and aphasia, seizures, mutism, coma, and death were not observed. All of the side effects ceased after 48- 120 hours cessation of treatment except fatigue which continued 7- 10 days after the cessation of therapy. "nConclusion: Ifosfamide has the power potential to produce both mild and severe neuropsychiatric side effects. A careful physical examination and early detection of these side effects can prevent major neuropsychiatric problems and rule out the necessity for specific treatment of those side effects and discontinuation of drug. "n "nKeyword: Ifosfamide, Neuropsychiatry, Side effects